Karakterisasi Faktor-faktor Virulensi Staphylococcus aureus Asal Susu Kambing Peranakan Ettawa secara Fenotip dan Genotip - Khusnan Khusnan; Wahyu Prihtiyantoro; Hartatik Hartatik; Mitra Slipranata (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Staphylococcus aureus is a major cause of mastitis in large or small ruminants, and often manifested by subclinical mastitis in Peranakan Ettawa (PE) goats. Staphylococcus aureus in human can cause food borne disease. The research aimed to characterize the virulence factors of Staphylococcus aureus isolated from milk PE goats, phenotypic- and genotypically. Phenotypically characterization were determined through the pigmen assay as well as hydrophobicity, haemolysin, and hemaglutinin reaction. Polymerase chain reaction (PCR) analysis was used to detect 4 virulen genes including coa, clf, fnbA, and fnbB genes. The results of research showed that Staphylococcus aureus abled to produce white pigmen (35,7%), yellow pigmen g (57,1%), andorange pigmen (7,2%). Staphylococcus aureus showed α-hemolysis zone (35,7%), β-hemolysis (35,7%), dan γ-hemolysis (28,9%). Hydrophobicytic test revealed 14,3% Staphylococcus aureus isolates were hydrophobe and85,7% hydrophil. Staphylococcus aureus (85,7%) isolates abled to aglutinated sheep blood cells. Based on genotypic analysis of Staphylococcus aureus could be detected coa gene (92,8%), clf gene (64,3%), fnbA gene (78,6%), and fnbB gene (64,3%). Based on the phenotypic and genotypic characters, it can be concluded that Staphylococcus aureus are virulent strains. This information can be used as the basis for control mastitis in PE goats